Diagnosis And Clinical Course of Chronic Generalised Periodontitis in Connective Tissue Dysplasia - Azimova Gulnoza Usmanovna; Ismailov Said Ibragimovich (Genius Journals, 2022)
This article discusses the analysis of the influence of behavioral factors and self-control of type 2 diabetes mellitus on the development of purulent-necrotic process of the lower extremities.
Keywords: pus; necrotic; process; development